2007
DOI: 10.1590/s0124-00642007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus en Niños Menores de Cinco Años. Patrones de Circulación, Características Clínicas y Epidemiológicas en Colombia, 1997-2003

Abstract: The data suggested that respiratory infection due to adenovirus was a low frequency event amongst the children seeking medical care at the sentinel hospitals. However, when respiratory disease was caused by adenovirus, it was severe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
2
4
0
7
Order By: Relevance
“…This lack of seasonality of HAdv infection has been described in other South American countries such as Colombia [38], Chile [44], and Brazil [54]. Nevertheless, we noted certain periods, such as the latter half of 2008, when either the absolute number or the proportion of HAdv identified (per total number of ILI cases) were elevated.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This lack of seasonality of HAdv infection has been described in other South American countries such as Colombia [38], Chile [44], and Brazil [54]. Nevertheless, we noted certain periods, such as the latter half of 2008, when either the absolute number or the proportion of HAdv identified (per total number of ILI cases) were elevated.…”
Section: Discussionsupporting
confidence: 73%
“…We also found that 5.3% of children younger than 5 years with ILI or SARI were infected with HAdv, a finding similar to many other South American HAdv studies. In Colombia, 2.6% (47/1743) of respiratory samples from children under 5 with ILI or SARI contained HAdv [38]. In Brazil, samples collected from pediatric patients with ILI or SARI (<5 years old) demonstrated a broad range of proportions containing HAdv: 6.8% (23/336) in São Paulo [39], 6.0% (52/862) in Rio Grande do Sul [40], and 2.3% (11/482) in Salvador, Bahia [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se identificaron adenovirus en 5,9 % de los menores de 5 años con IRA en Bucaramanga en ambas estaciones, cercano a la prevalencia reportada en hospitales centinela de Bogotá y Manizales entre 1997-2003, donde se presentó de manera constante durante todos los meses del año, con un aumento en marzo, julio, octubre y diciembre (26).…”
Section: Discussionunclassified